Participation in decision-making within prison settings as a tool for enhancing the enjoyment of the right to health: The case of women inmates in Zambia - Nkhata, Chipo Mushota (Department of Public Law, 2025)
The number of women inmates is growing exponentially globally, with sub-Saharan Africa experiencing an annual growth rate in the prison population of 22%. Many correctional facilities and prisons were not designed or built with women in mind. This has seen women excluded in many aspects of correctional and penal systems including in correctional health systems. The situation is no different for Zambian women inmates who have limited access to health facilities, goods, services, and programmes. Women inmates in Zambia have one of the lowest citizenship status' in the country owing to the multiple levels of discrimination that they experience including discrimination based on their gender and their legal status as inmates. For many years, women inmates were rendered invisible in the Zambian correctional and penal system and in the general population and treated as non-existent. The growing recognition of women's rights, the paradigm shifts from punitive to a hybrid of a punitive and correctional system, and the growing involvement of citizens in governance in Zambia, present an opportunity to re-evaluate the situation of women inmates and put in place measures that effectively integrate them as full members of the Zambian society, entitled to enjoy fundamental rights and freedoms such as health and citizenship. This thesis sets out to establish whether participation in health-related decision-making and programmes by women inmates would enhance their enjoyment of the right to health. Existing literature shows that citizenship participation is an appropriate vehicle for fostering citizens' effective participation in governance for the attainment of their rights and interests. While most interventions focus on citizenship participation as a political tool, I leverage the argument that citizenship participation is equally useful in advancing social rights and interests such as health. I use a qualitative research methodology to engage key stakeholders such as women inmates, their representative institutions, and governmental and quasi-governmental institutions to ascertain the desirability and feasibility of using the citizenship participation model to enhance women inmates' health rights. This methodology is also used to ascertain the role of the Zambian regulatory framework in realising such participation. Many study respondents in this study stated that women inmates' participation in health related decision-making and programmes is cardinal to the realisation of their right to health as envisaged under international and human rights frameworks. However, for women inmates to participate effectively in health governance, I argue that it is necessary to employ a model to citizenship participation that ensures their effective integration in health governance systems of the Zambia Correctional Service. Through the study respondents' views, I establish that traditional approaches to governance, including the rights-based and feminist approaches offer an entry point for women inmates' participation in health governance but are not entirely suitable for responding to their health needs and experiences. To address this gap, I propose a model that I term “a woman-centred citizenship participation model” for health. Through this model, the State should seek to solicit women inmates' effective and active participation in health governance in their correctional centres in Zambia.